Cervicovaginal Smear Findings of Endometrial Serous Carcinoma: A Case Report - Figen Barut; Şükrü Oğuz Özdamar; Aykut Barut; Ülkü Bayar; Sibel Bektaş; Burak Bahadır; Banu Doğan Gün (Medical Network, 2008)
An endometrial serous carcinoma case which is a variant of endometrial carcinoma exhibiting an agressive course that has been detected by cervicovaginal smear, is presented in this report in light of the datas of the related literature. No particular sign has been observed during the gynecological examination of the 77-year-old patient who applied to university hospital with the complaints of vaginal discharge and perineal pruritus. Cervicovaginal smear showed atypical glandular cells, exhibiting seldom bare nuclei and papillary clusters in most of the areas with a necrotic background. By the help of those cytopathological findings, the diagnosis was "Epithelial cell abnormality: atypical glandular cells (AGC) in favour of neoplasia and atypical squamous cells of undetermined significance (ASCUS) and due to "possiblity of an adenocarcinoma", cervical and/or endometrial biopsy was recommended. The result of the endometrial biopsy was reported as "serous papillary adenocarcinoma". Postoperatively, examination of hysterectomy material revealed an infiltration of "endometrial serous carcinoma" extending towards cervix, myometrium, and serosa, and full filling the endometrial cavity. The case, regarded as Stage IV died on postoperative 13th day. Although cervicovaginal smear generally is not a sensitive screening test for endometrial carcinomas, it played an important role in determining serous carcinoma. This may be related with advanced stage and/or aggressive features of the neoplastic process.